PENGARUH SOCIAL PROOF TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PASCA MERGER TIKTOK SHOP DAN TOKOPEDIA DI KOTA MAKASSAR - Nurdin, Nasyirah; Musmahendra, Musmahendra; Rumissing, Dodi; Riyadi, Syamsul; Sari, Novita Kumala; Haritza, Dita (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to find out and analyze the influence of Social Proof on consumer purchase decisions after the merger between TikTok Shop and Tokopedia, especially in Makassar City. This study uses a descriptive quantitative approach that aims to reveal the influence between Social Proof variables (such as reviews, ratings, number of buyers, and the influence of public figures) on consumer purchasing decisions. The population of this study is the entire population of Makassar City totaling 1,474,393 people, with a sample of 100 respondents selected using the purposive sampling technique. Data was obtained through a questionnaire survey designed to measure respondents' perception of the influence of Social Proof on their purchasing decisions. The data analysis technique was carried out with the help of SPSS software to see the significant relationship between the two variables. The results showed that there was a strong relationship between Social Proof and consumer purchase decisions, with a significant value of 0.001 which was smaller than 0.05. This indicates that Social Proof has a significant influence on consumer purchase decisions after the merger in Makassar City, so the strategy of using social proof can be an effective marketing tool for the company.